Etika Al-Qur’an Terhadap Non-Muslim - Harda Armayanto (TSAQAFAH, 2013)
This paper describes the ethics toward non-Muslims based on al-Qur’an. Islam as a religion of peace was accused and insulted by the orientalists frequently. These accusations and insulting stated in several articles, journals either in their books. Their books like Islamic Invasion wrote by Robert Morey and Islam Revealed by Anis A Shorrosh are some sample of how the orientalists discredits Islam. Whereas Islam is not like what they accused. On the contrary, Islam has responding their accusations with an elegant and tolerant doctrine. Islam has teaches its peoples to respects another religion’s people, Islam forbids his people to insult other religions, to excoriate their worships or forcing non-Muslims to convert  or believes  to Islam, even  Islam teaches  its  people to acknowledge non-Muslims  as  brother  and  sister.  This  is  Islam’s  admiration  toward  non- Muslims. Surprisingly, these admirations inversely proportional to what non- Muslims did toward Islam and its people. The abuses as what we mention it before, was being happened even until now. Lately, one of  Christian pastor in United State was told his people to burn the Holly Qur’an or as we known about suppression of Rohingya’s Muslims that was did by Myanmar’s Buddhists.